Ipilimumab: A potential immunologic agent in the treatment of metastatic castration-resistant prostate cancer - Kittai, Adam (Landes Bioscience, 2014)
Immunotherapy has garnered an important place in the therapeutic landscape of treatment in prostate cancer since approval of sipuleucel-T. Ipilimumab is a checkpoint inhibitor that is currently approved for the treatment of advanced melanoma. In the June issue of Lancet Oncology, Kwon and colleagues report the phase III trial using ipilimumab in a post-docetaxel metastatic castration-resistant prostate cancer population. While the primary endpoint of overall survival was not met, several lessons are learned from the analysis of this trial. Perhaps better refinement of a more favorable group of patients who may potentially benefit from an immunologic treatment should be advocated.